The Role of Cutibacterium acnes in the Etiopathogenesis of Sarcoidosis: Current Insights and Future Study Directions - Di Francesco, Angela Maria; Pasciuto, Giuliana; Verrecchia, Elena; Sicignano, Ludovico Luca; Gerardino, Laura; Rigante, Donato; Manna, Raffaele (International journal of molecular sciences, 2025)
Cutibacterium acnes (C. acnes) is a commensal bacterium of the skin microbiota that can transform itself into a pathogen depending on the peculiar susceptibility of the host: it is the sole microorganism so far to be found in the specific organ lesions of sarcoidosis, and C. acnes-induced activation of T-helper-type-1 cell responses is generally higher in patients with sarcoidosis than in healthy subjects. This bacterium acts as an opportunistic agent in several inflammatory conditions other than sarcoidosis, such as prostate cancer and prosthetic joint infections. Both innate and adaptive immunity systems are involved in the pathogenesis of C. acnes-mediated sarcoid lesions, and a seminal role is played by host toll-like receptor (TLR)-2, TLR-4, TLR-6, NOD-like receptors, and mononuclear cell cytoplasmic receptors. This review summarizes current knowledge on the potential cause–effect relationship existing between C. acnes and sarcoidosis, addressing issues of future research directions and novel therapeutic strategies in the management of a complex disease such as sarcoidosis.